Why the Microfinance Institutions exist: Lending groups as a mechanism to enhance informational symmetry and enforcement activities - Marconatto, Diego Antônio Bittencourt; Cruz, Luciano Barin; Moura, Gilnei Luiz de; Teixeira, Emidio Gressler (Organizações & Sociedade, 2017)
In this paper, we focus on the economic motivation for the existence of microfinance institutions (MFIs). In doing so, our study contributes to the debate regarding why MFIs exist and, especially, what mechanisms are used to address the risks associated with their operation. In examining the reasons why some individuals are regarded as “non-bankable”, we lay out the basic economic logic that motivates the exclusion of this population from formal credit markets. Next, we show how the lending group methodology overcomes the credit dilemma which sustains and increases the exclusion of the poorest from these formal credit sources. Through this development, we point to the microfinance founding mechanisms: the increase of both the informational symmetry and the enforcement capacity of MFIs through the enhancement of their screening, monitoring and enforcement activities. We also highlight the importance of context and gender for the success of lending groups. Finally, we analyze these mechanisms in the Brazilian context.